Monoclonal gammopathy of undetermined significance in systemic transthyretin amyloidosis (ATTR). (2nd January 2018) - Phull, Pooja; Sanchorawala, Vaishali; Connors, Lawreen H.; Doros, Gheorghe; Ruberg, Frederick L.; Berk, John L.; Sarosiek, Shayna
Abstract: Objective: To identify the prevalence of monoclonal gammopathy of undetermined significance (MGUS) in patients with transthyretin (ATTR) amyloidosis. Patients and methods: We performed a retrospective analysis of patients with biopsy-proven ATTRwt (wild-type transthyretin amyloid protein) and genopositive ATTR V122I (valine-to-isoleucine substitution at position 122 of the TTR gene) amyloidosis evaluated at the Amyloidosis Center at Boston University and Boston Medical Center between 1 January 2003 and 31 December 2016. Results: There were a total of 226 patients with ATTRwt and ATTR V122I amyloidosis evaluated during the specified time frame with 155 and 71 patients in each cohort, respectively. Those with complete medical records, 140 patients with ATTRwt and 57 V1221 ATTRm subjects, were included in the analyses. Fifty-five patients (39%) in the ATTRwt cohort and 28 patients (49%) in the ATTR V122I cohort had an MGUS, as indicated by an abnormality in the serum-free light-chain ratio and/or serum immunofixation electrophoresis. Conclusion: These data confirm the high prevalence of coexistent MGUS with ATTR amyloidosis in this patient population, with an MGUS rate that is higher than the general population. These findings also highlight the importance of a thorough diagnostic evaluation in patients with amyloidosis to determine the precursor protein, as the clinical course and treatment of AL (light-chain amyloid protein) and ATTR amyloidosis are distinct.